Removal of lead from wastewater using agricultural byproduct wheat bran - Singh K.K.; Singh N.L.; Hasan S.H. (My University, 2025)
Wheat bran a low cost biosorbent has been used for the removal of Lead (II) from wastewater. Maximum removal of lead (II) was found to be 96.6% at pH 6.5, initial Pb (II) concentration of 40 mg/L and temperature of 20°C. The effect of different parameters, such as contact time, adsorbate concentration, pH of the medium and temperature were investigated. Dynamics of the sorption process were studied and the values of rate constant of adsorption, pore diffusion coefficient and mass transfer coefficient were calculated. Different thermodynamic parameters, namely changes in standard free energy, enthalpy and entropy have also been evaluated and it has been found that the reaction was spontaneous and exothermic in nature. The applicability of Langmuir isotherm showed of monolayer coverage of the adsorbate on the surface of adsorbents. A generalised empirical model was proposed for the kinetics at different initial concentration. The data were subjected to multiple regression analysis and a model was developed to predict the removal of Pb (II) from wastewater. © 2005 - Kalpana Corporation.